Orthopaedic Guidelines for the COVID-19 Post-Outbreak Period: Experience from Wuhan, People's Republic of China. (5th August 2020) - Xiong, Yuan; Chen, Lang; Lin, Ze; Panayi, Adriana C.; Mi, Bobin; Liu, Guohui
Abstract : Abstract: Currently, the coronavirus disease 2019 (COVID-19) crisis has rapidly spread worldwide. As the earliest outbreak area of the pandemic, Wuhan, People's Republic of China, is gradually recovering to its normal state under the effective control of government authorities. Outpatient services in major hospitals are now being restored. An accumulation of asymptomatic infections is a potential risk for medical personnel, especially when there is crowding in hospitals. As the biggest center for orthopaedic patients in Wuhan, our orthopaedic outpatient department admits >300 patients per day. Optimal guidelines on how to handle this huge number of patients during the post-outbreak stage of the COVID-19 pandemic, particularly with regard to potential asymptomatic infection, are urgently needed for orthopaedic surgeons. We have developed and proposed applicable guidelines to fill this knowledge gap, including the necessary protective strategies for medical personnel in orthopaedic outpatient and inpatient wards as well as during surgery. We also have provided mental health recommendations for health-care workers. To the best of our knowledge, these guidelines are the first of their kind for orthopaedic surgeons who are slowly reestablishing medical activity following the pandemic.